Legal Certainty Regarding the Inclusion of Unrecorded Marriages on Family Cards - Lulu Salsabila Sudarmo; Fence M Wantu; Weny Almoravid Dungga (Lambung Mangkurat Law Journal, 2026)
This study examines the legal certainty of including the status of "unregistered marriage" in the Family Card from a normative juridical perspective with a statutory, conceptual, and casuistic approach, revealing fundamental inconsistencies between the substantive formalism of Law Number 1 of 1974 concerning Marriage which requires registration as an absolute requirement for the legal force of marriage (Article 2 paragraph 2) with the administrative descriptive approach of Law Number 24 of 2013 concerning Population Administration which accommodates the social reality of unregistered marriage through a Statement of Absolute Responsibility based on the Regulation of the Minister of Home Affairs Number 109 of 2019. The results of the analysis show that this normative dualism gives rise to the ambiguity of the hierarchy of norms as stipulated in Article 7 of Law Number 12 of 2011 concerning the Establishment of Legislation, moral hazard in marriage registration practices, and permissive Dukcapil field practices with tens of thousands of families with this status every year. The legal implications for the protection of wives' civil rights include the vulnerability of the right to maintenance (Article 34 of the Marriage Law), joint property, and limited inheritance (KHI Article 171), while for children it creates weak legal filiation resulting in the status of "one mother's child", hampered education rights, and the risk of statelessness which is contrary to the Convention on the Elimination of All Forms of Discrimination Against Women, the Convention on the Rights of the Child 1989, and Articles 27-28 of the 1945 Constitution. Critical discussions through grammatical, systematic, teleological, and comparative interpretations confirm that the status of "unregistered marriage" violates the principle of rechtszekerheid, creates structural gender injustice, and institutionalizes administrative exploitation. As a novelty, the research proposes the concept of "integrated administrative itsbat" through a national digital platform that integrates the Population and Civil Registration Office-Religious Affairs Office-Religious Court with artificial intelligence-based validation of Absolute Responsibility Statements and a mandatory 90-day timeline, revolutionizing the protection of marginalized families through inclusive technology